Secrets of Quick Learning of a Foreign Language - Eshonkulova Madina Sanjar qizi (Research Parks Publishers, 2022)
Life today cannot be imagined without foreign languages. As the process of globalization accelerates, learning a foreign language is becoming a modern requirement. Today, knowing English has become a simple requirement to be a good professional in any field. The question I asked myself while learning a foreign language was: